Impact of Formative Assessment on Students’ Motivation in Foreign Language Acquisition - Dmitrenko, Natalia; Budas, Iuliia; Koliadych, Yulia; Poliarush, Nina (East European Journal of Psycholinguistics, 2021)
The article focuses on introducing formative assessment to the educational process of professionally oriented English communication and the impact of assessment on students’ motivation to learn English. In the article, various types of motivation are discussed; high and low levels of formative assessment are presented; the relationship between motivation and assessment in learning English is studied. The model of high and low levels of formative assessment implementation in learning English for professional communication is tested. The levels of students’ motivation to English acquisition in the conditions of low and high levels of formative assessment are compared. Special attention is paid to specific pedagogical conditions under which formative assessment has a greater impact on students’ motivation. Experimental training was conducted among students of the pedagogical university who study English for professional communication. The authors compare and analyze the results of the motivation tests and diagnostic tests of language proficiency at the pre- and post- stages of experimental training. The study supports the idea about the relationship between students’ motivation and their English language proficiency assessment. The results show that a high level of formative assessment can be beneficial for overcoming students’ low motivation if students receive immediate feedback, evaluation of their work, teachers’ recommendations and support. It is observed that the reasonable integration of students’ self-assessment into teachers’ formative assessment plays a vital role in increasing students’ motivation to English acquisition. According to the study, regular practical implementation of high-level formative assessment methods in English acquisition increases the level of students’ motivation and, consequently, the level of students’ achievements in mastering professionally oriented English communication.